Nd: YAG and pulsed dye laser therapy in infantile haemangiomas; a retrospective analysis of 271 treated haemangiomas in 149 children - Hartmann, Franziska; Hänßle, Holger (Journal of the European Academy of Dermatology and Venereology, 2017)
Background Infantile haemangiomas (IH) are common benign tumours in infancy. Most IH resolve spontaneously, but some require treatment due to ulceration, functional impairment or cosmetic disfiguration. While systemic propranolol is effective in many cases, laser therapy may be a safe topical alternative. Objective To assess the efficacy of combined Nd:YAG/pulsed dye laser (PDL) or PDL alone for therapy of IH. Patients and methods A total of 271 IH in 149 infants were treated with combined Nd:YAG/PDL or PDL alone. Based on photographs before and 4-6 weeks after the last treatment, the results were evaluated independently by three physicians. Remissions were categorized as 0-25% (I), 26-50% (II), 51-75% (III) and 76-100% (IV). Results In total, 472 laser treatments were performed. In 137 of 149 infants (91.9%) laser therapy was performed during a short sevoflurane mask anaesthesia, while 12 of 149 infants (8.1%) received topical anaesthetic gel. Combined Nd:YAG/PDL was applied in 187 of 271 IH (69.0%), while PDL alone in 84 of 271 IH (31.0%). On average, 1.74 treatments per IH were necessary (Nd:YAG/PDL: 1.95, PDL: 1.26). Moderate or strong (III/IV) improvement was observed in 92.4% of all IH treated. No serious adverse effects were observed. Conclusion Combined Nd:YAG/PDL therapy is an effective and well-tolerated local treatment option for IH of any classification, in any phase of development and at any age. With regard to the systemic use of propranolol, combined Nd:YAG/PDL therapy seems a safe and promising alternative in many cases.